Judges' Considerations in Assessing the Criteria for Class Action Lawsuits during the Covid 19 Pandemic Based on Supreme Court Regulation Number 1 of 2002 concerning Class Action Lawsuits (Study of Decision Number: 581/Pdt.G/2020/Pn/Mdn) - Sahala Pardamean Harahap; Risdalina Risdalina; Indra Kumalasari M (Budapest International Research and Critics University, 2022)
This study aims to determine the judge's considerations in assessing the criteria for Class Action lawsuits in accordance with Supreme Court Regulation No. 1 of 2002 concerning Class Action Lawsuit Procedures. This research is descriptive normative legal research with a case approach. This study uses the types and sources of legal materials consisting of primary legal materials and secondary legal materials. The Class Action lawsuit filed must be examined first and must meet the criteria for a class action lawsuit before the trial is held. The lawsuit in the Decision has met the three criteria for a Class Action lawsuit in the Supreme Court Regulation Number 1 of 2002 concerning Class Action Lawsuit Procedures. Based on the results of the research and discussion, it can be concluded that the lawsuit filed in the decision has met the criteria for a Class Action lawsuit, but there are differences in the fulfillment of the class action criteria in the decision, including the criteria for numeriousity, commonality and typicality, and adequacy of representation. The legal consequences if the lawsuit does not meet the criteria to be examined as a Class Action lawsuit, namely the lawsuit is declared invalid, the case examination is terminated, the lawsuit is declared unacceptable, and the losing party is punished to pay the court costs incurred.